PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR CAMAT AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA. - Raudah, Siti; Sarnubi, Muhammad Said (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The problems found at the Central Amuntai District Office are the lack of attention and ability of employees in the form of providing information to visitors, so that there is often a misunderstanding between visitors and service employees, lack of accuracy and awareness in providing good service and helping visitors who need help, and lack of. This research uses a Quantitative approach with a causal associative type and explains systematically. The data collection techniques used are observation, questionnaires and documentation. Data sources were taken using the Slovin formula and sampling techniques totaling 75 respondents. The results showed that the results that the Service Quality variable (X) had a significant effect on the Community Satisfaction variable (Y) at the Central Amuntai Sub-District Office, HSU Regency. This can be seen from the level of satisfaction as evidenced by the simple linear regression analysis Y = 22.294 + 0.089 X, which means that every one increase in Service Quality has an effect of 0.089 on Community Satisfaction, so there is an influence between variable X and variable Y. Meanwhile, from the results of the t test calculation, namely the tcount of 2, 438 compared to the t table (db = 73) which is 2, 379 with a significant level of 0.01, this means that tcount> t table, Ha is accepted and Ho is rejected and Ha1 is accepted. means that there is a positive and significant influence between Service Quality on Community Satisfaction at the Central Amuntai Sub-District Office of Hulu Sungai Utara Regency.